GROWTH APPROACH IN ALLIANCE THE ANIMATION COMMUNITY OF MALANG CITY (International Conference of Graduate School on Sustainability (ICGSS), 2018)
This study is part of the dissertation research, aimed at uncovering the interaction dynamics of the telematics creative community in Malang city, because it can open-up a new understanding of the uniqueness of growth pattern. The urgency is intended to be able to describe in detail and naturally, especially regarding the interactive patterns of the animation community, that have cultural relations with industrialist as the actors. Everything goes from the awareness of industrialist, that the national and local animation business will experience ups and downs, that are difficult to control, if not supported by the mover of animation community. This evolutionary development can be followed since April 1, 2016, which coincides with the declared Creative City International Conference (ICCC) in the city of Malang. This condition can be described as a directed social movement, and is controlled by social norms, that are more dominant than only business interests. For this reason, the exploratory study with grounded-preparation approach, which is strengthened by synthesis-literacy, seeks to prioritize an inductive pattern based on empirical-deduction, so as to establish the animation community of Mocca Animation Studio, as truly worthy of being the target of the research. The study has been prepared and carried out for more than 2 year, shows the actors of industry are always trying to open facilitation for community, to increase capacity building, and support continuously to develop production innovation. The animation industry obtains multiple benefits: (1) strengthening of individual characters, that are reflected in every action related to the work of innovation; (2) there are efforts based on togetherness, to maintain the existence of the animation community; (3) the increasing number of animation movers, who grew up in the form of small alliances in the unity of the system.